The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5507/fot.2016.026
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of freshwater dinoflagellates in the State of Paraná, southern Brazil, with taxonomic and distributional notes

Abstract: Dinoflagellate taxonomy has been undergoing a comprehensive review in recent decades. Knowledge on Brazilian dinoflagellate flora remains quite incomplete, particularly regarding the size of the country. This study is the first taxonomic survey of freshwater dinoflagellates in the State of Paraná, southern Brazil. Fortyone freshwater environments were sampled in Paraná and two others on the border between Paraná and Santa Catarina during 2010-2015, and 21 dinoflagellate taxa assigned to 13 genera were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
(13 reference statements)
0
4
0
3
Order By: Relevance
“…Worldwide Floristic studies on thecate dinoflagellate ensembles have reported richness from seven to twenty-two species (Ling et al, 1989;Carty, 1993;Borics et al, 2005;Hansen and Flaim, 2007;Cavalcante et al, 2017). This study, despite studying fewer systems ( 14), yielded evidence for a relative floristic richness (13 spp.)…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Worldwide Floristic studies on thecate dinoflagellate ensembles have reported richness from seven to twenty-two species (Ling et al, 1989;Carty, 1993;Borics et al, 2005;Hansen and Flaim, 2007;Cavalcante et al, 2017). This study, despite studying fewer systems ( 14), yielded evidence for a relative floristic richness (13 spp.)…”
Section: Discussionmentioning
confidence: 71%
“…The limited number of studies conducted in freshwater ecosystems reflects the lack of knowledge about continental dinoflagellates' ecological requirements (Grigorszky et al, 2003a;Rengefors and Kremp, 2018). Thus, the most relevant studies have emphasized community composition, geographical distribution, and blooms (Boltovskoy, 1983;Ling et al, 1989;Cavalcante et al, 2013Cavalcante et al, , 2017Craveiro et al, 2015). Although the biogeographical pattern distributions have not been unveiled, relevant information about the species' biology and life histories has been discussed (Pollingher, 1987;Moestrup and Calado, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peridiniopsis presenta una amplia distribución mundial (Krakhmalny et al 2000, Zhang et al 2012, Carty 2014, Moestrup & Calado 2018. En América del Sur los estudios taxonómicos enfocados en los dinoflagelados de ecosistemas acuáticos continentales son limitados (e.g., Boltovskoy 1973, 1975, 1999, 2003, Ascencio et al 2015, Samanez 2015, Cavalcante et al 2017) y concretamente los reportes de especies de Peridiniopsis son muy escasos (Meyer et al 1997, Boltovskoy 1999, Cavalcante et al 2017.…”
unclassified
“…As amostras para análise quantitativa do fitoplâncton, obtidas nas duas profundidades Bicudo, 2007); Dinophyceae (Bicudo, 2011;Cavalcante et al, 2017); Coscinodiscophyceae (Bicudo et al, 2016;Lehmkuhl et al, 2010); Bacillariophyceae (Brassac;Ludwig, 2003;Bicudo, 2008;Marquardt;Costa et al, 2017;Morais et al, 2018); e demais bibliografias especializadas para grupos menos frequentes. A análise taxonômica foi baseada nas características morfométricas de amostras populacionais (mínimo de 20 indivíduos), exceto as espécies raras.…”
Section: Variáveis Biológicas Da áGuaunclassified